Appraisal of the Free Ulnar Flap Versatility in Craniofacial Soft-tissue Reconstruction. Issue 9 (September 2018) - Kantar, Rami S.; Rifkin, William J.; Cammarata, Michael J.; Jacoby, Adam; Farber, Scott J.; Diaz-Siso, J. Rodrigo; Ceradini, Daniel J.; Rodriguez, Eduardo D.
Abstract : Summary: The unique anatomical characteristics of the forearm region make it especially popular as a free flap donor site for craniofacial soft-tissue reconstruction. The free ulnar forearm flap is less hirsute and allows for better concealment of donor site scar as compared with its radial counterpart. Despite these factors, the free radial forearm flap remains more popular among reconstructive surgeons. Through the presented case series, we hope to emphasize the versatile nature of the free ulnar forearm flap in addressing various craniofacial soft-tissue defects. Following institutional review board approval, a retrospective review of the senior authors' clinical experience performing microvascular free ulnar forearm flap reconstruction of craniofacial soft-tissue defects was performed. A total of 10 patients were identified through our review. Soft-tissue defect locations included lower eyelid (n = 2), tongue and floor of mouth (n = 2), lower lip (n = 2), palatopharyngeal area (n = 1), nose (n = 1), and palate (n = 1). Trauma was the most common defect etiology (n = 5), followed by malignancy (n = 4), and iatrogenic injury in 1 case. All patients demonstrated good aesthetic and functional outcomes related to vision, speech, and oral intake at follow-up when applicable. The free ulnar forearm flap is a versatile reconstructive option that can be used to address a wide spectrum of craniofacial soft-tissue defects and offers numerous advantages over its radial counterpart.